Exploring Freshman Students’ Perceptions of Using IPA Symbols in English Pronunciation Class - Yumnaa Taqiyatul Nabillah; Diah Kusuma Ningrum; Wahyu Indah Mala Rohmana (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This present research investigates the perceptions of freshman English education students regarding the use of IPA symbols in English pronunciation classes. The selection of participants is carried out through purposive sampling. The research employs a descriptive qualitative research approach, focusing on ten students of Class C from the English Education Department at Universitas Islam Negeri Maulana Malik Ibrahim Malang. The data is collected by unstructured interviews via WhatsApp and analyzed using thematic analysis. The results show that Students encounter challenges when attempting to utilize the International Phonetic Alphabet (IPA) symbols, particularly in differentiating between similar sounds and adapting to unfamiliar symbols. However, the majority of students recognized the significant benefits of acquiring and utilizing knowledge of IPA symbols, including enhanced pronunciation accuracy, listening skills, and confidence in speaking English. This study emphasizes the value of integrating IPA symbols into language learning, which can facilitate the acquisition of accurate pronunciation and enhance language proficiency.